2019
DOI: 10.1186/s13100-019-0185-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex and the TEs: transposable elements in sexual development and function in animals

Abstract: Transposable elements are endogenous DNA sequences able to integrate into and multiply within genomes. They constitute a major source of genetic innovations, as they can not only rearrange genomes but also spread ready-to-use regulatory sequences able to modify host gene expression, and even can give birth to new host genes. As their evolutionary success depends on their vertical transmission, transposable elements are intrinsically linked to reproduction. In organisms with sexual reproduction, this implies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 138 publications
(172 reference statements)
7
66
1
Order By: Relevance
“…While it has been hypothesized that these chromosomes might be relevant for apomixis expression and in particular possible implications for diplospory have been discussed, transmission of a Het chromosome alone is not sufficient for apomixis to arise [23,59]. Interestingly, the Het chromosomes and heterochromatic chromosomal regions linked to apomixis resemble features of Y-chromosomes in animals and dioecious plants for sex determination with respect to typical accumulation of transposable elements and gene loss [29,46,60]. Therefore, it is tempting to speculate that similarly to well known mechanisms in Y-chromosomes, epigenetic regulatory mechanisms might be major driving forces in regulation of apomixis.…”
Section: Genetic Loci Linked To Apomixis Typically Represent Hemizygomentioning
confidence: 99%
“…While it has been hypothesized that these chromosomes might be relevant for apomixis expression and in particular possible implications for diplospory have been discussed, transmission of a Het chromosome alone is not sufficient for apomixis to arise [23,59]. Interestingly, the Het chromosomes and heterochromatic chromosomal regions linked to apomixis resemble features of Y-chromosomes in animals and dioecious plants for sex determination with respect to typical accumulation of transposable elements and gene loss [29,46,60]. Therefore, it is tempting to speculate that similarly to well known mechanisms in Y-chromosomes, epigenetic regulatory mechanisms might be major driving forces in regulation of apomixis.…”
Section: Genetic Loci Linked To Apomixis Typically Represent Hemizygomentioning
confidence: 99%
“…brevicornis, A. mellifera, and N. vitripennis (Dechaud et al 2019). Also, tra/fem duplications have been shown in CSD systems before, most notably in A. mellifera where a fem gene duplication event resulted in it becoming a csd locus (Hasselmann et al 2008;Gempe et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Selfish endosymbionts can cause feminization of genetic males, and microbe‐induced parthenogenesis regularly occurs in arthropods (Kageyama, Narita & Watanabe, 2012) (Kageyama et al , 2012). It is also suggested that TEs through their influence on the expression of sexual development genes, often with pronounced sex‐specific effect, can influence sex determination including sex chromosome evolution (Dechaud et al , 2019). Hence, a variety of SGEs has a major influence on the evolutionary dynamics of sex chromosomes.…”
Section: Selfish Genetic Elements Affect Sex Determinationmentioning
confidence: 99%
“…Moreover, many SGEs whilst not causing sex ratio distortion also have sex‐specific effects. For example, many TEs show pronounced sex‐specific activity (Dechaud et al , 2019). The differential expression of SGEs in males and females has the potential to generate sexual conflict through their potentially sexually antagonistic effect.…”
Section: Selfish Genetic Elements Can Generate Sexual Conflict and Sementioning
confidence: 99%
See 1 more Smart Citation